Nonlinear Pushover Analysis Of Reinforced Concrete Structures With Basalt Fiber Reinforcement In Seismic Zones - Alfana, Siril (Innovative Research in Civil and Environmental Engineering, 2025)
This study investigates the seismic performance of reinforced concrete (RC) structures with basalt fiber reinforcement (BFRC) using nonlinear pushover analysis. The main objective is to evaluate the effect of basalt fiber reinforcement on the seismic response of RC structures located in earthquake-prone regions. The analysis focuses on key seismic parameters, including base shear, displacement, energy dissipation, and crack propagation. The results show that BFRC structures exhibit significantly enhanced seismic performance compared to conventional RC structures. The BFRC structures demonstrated higher base shear capacity, greater displacement capacity, improved energy dissipation, and better crack resistance. These improvements suggest that basalt fiber reinforcement can effectively enhance the ductility and strength of concrete structures, making them more resilient to seismic forces. The study highlights the potential of BFRC as a sustainable and efficient material for improving the seismic resilience of buildings in high seismic zones.